2016
DOI: 10.1534/g3.115.025197
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Gene Tree Variation to Identify Candidate Effector Genes in Zymoseptoria tritici

Abstract: Zymoseptoria tritici is a host-specific, necrotrophic pathogen of wheat. Infection by Z. tritici is characterized by its extended latent period, which typically lasts 2 wks, and is followed by extensive host cell death, and rapid proliferation of fungal biomass. This work characterizes the level of genomic variation in 13 isolates, for which we have measured virulence on 11 wheat cultivars with differential resistance genes. Between the reference isolate, IPO323, and the 13 Australian isolates we identified ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…As for the in vitro experiments, no strains 166 lacking more than one chromosome were found. Interestingly, chromosome 18, which was 167 found to be lost at high rates in our plant experiments, was shown to be frequently absent 168 in field isolates of Z. tritici (Croll et al 2013;McDonald et al 2016). In summary, our findings 169…”
Section: Introduction 31mentioning
confidence: 74%
“…As for the in vitro experiments, no strains 166 lacking more than one chromosome were found. Interestingly, chromosome 18, which was 167 found to be lost at high rates in our plant experiments, was shown to be frequently absent 168 in field isolates of Z. tritici (Croll et al 2013;McDonald et al 2016). In summary, our findings 169…”
Section: Introduction 31mentioning
confidence: 74%
“…Therefore, such genes may be located in genome compartments unique to individual genomes. A previous study identified reference genome genes which were likely missing in 13 sequenced Australian isolates (35). Using BLAST, we searched for genes in the IPO323 genome that were absent in the 3D7 genome.…”
Section: Resultsmentioning
confidence: 99%
“…Genes encoding SSPs evolved more rapidly than the genomic background (25, 34) and were more likely to lack orthologs in closely related species (33). Genomic analyses suggested that numerous genes (including effector genes) were deleted in at least some isolates of the species (31, 35). …”
Section: Introductionmentioning
confidence: 99%
“…For comparison, population genomic sequencing of 13 isolates of Z. tritici sampled from one region in Australia showed more than 800 000 SNPs [56]. Although the number of polymorphic nucleotides was found to be relatively low, the 11 isolates of V. dahliae were found to exhibit a dramatic variation in their genome composition and genome content.…”
Section: Example 2: Hybridization Of Crop Plants Driving Hybrid Specimentioning
confidence: 99%